Ursolic acid inhibits epithelial-mesenchymal transition in vitro and in vivo - Chang-Geng Xu; Xia-Lian Zhu; Wei Wang; Xiang-Jun Zhou (Taylor & Francis Group, 2019)
Context: Ursolic acid (UA; 3β-hydroxy-urs-12-en-28-oic acid), one of the pentacyclic triterpenoids found in various plants and herbs, possesses some beneficial effects under pathological conditions, including combating hepatic fibrosis. Objective: This study investigates the effects of UA on renal tubulointerstitial fibrosis in vivo and in vitro. Materials and methods: In vivo, 24 male C57BL6 mice were divided into four groups. Eighteen mice were subjected to unilateral ureteral obstruction (UUO) and the remaining six sham-operated mice served as control. UUO mice received either vehicle or UA (50 or 100 mg/kg) by gastric gavage for 6 days. In vitro, HK-2 cells were treated with 10 or 50 μM UA and 10 ng/mL recombinant human transforming growth factor-β1 (TGF-β1). The molecular mechanisms of fibrosis were investigated. Results: UUO induced marked interstitial collagen I and fibronectin deposition and epithelial-mesenchymal transition (EMT), as evidenced by increased α-smooth muscle actin (α-SMA) and decreased E-cadherin. However, UA treatment significantly reduced collagen I and fibronectin accumulation in the fibrotic kidney. UA treatment also decreased α-SMA and preserved E-cadherin in vivo. In vitro, TGF-β1-treated HK-2 cells demonstrated elevated α-SMA, snail1, slug, TGF-β1, and p-smad3, as well as diminished E-cadherin. UA pretreatment prevented E-cadherin loss and diminished α-SMA expression in HK-2 cells. UA downregulated mRNA expression of snail1 and slug. UA also lowered TGF-β1 protein expression and p-Smad3 in HK-2 cells. Conclusions: UA attenuated renal tubulointerstitial fibrosis by inhibiting EMT, and such inhibition may be achieved by decreasing profibrotic factors. UA may be a novel therapeutic agent for renal fibrosis.